Management Survey at the Arema Ngunut Academy, Tulungagung Regency, 2023-2024 - Ramadhan, Ryan Rachmat; Yuliawan, Dhedhy; Burstiando, Rizki (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This study aims to analyze the management and performance development process of the Arema Ngunut Football Academy School (SSB) in Tulungagung Regency, which has seen a decline in student numbers each year. Using a descriptive qualitative approach and survey method, this research involves the organization’s chairman and head coach as subjects. Data collection was conducted through in-depth interviews, observations, and documentation from February to April 2024, with data validity tested using source triangulation techniques and data analysis through an interactive model. The results indicate that the SSB management is run by the general chairman, secretary, treasurer, and coaches. Performance development is carried out in a tiered and sustainable manner, without initial selection, with training sessions held three times a week. Students are charged a fee per session as the main source of funds, in addition to operational funds from the local government. The main challenge in performance development is the full-day school system, which reduces student training consistency and impacts the operational funding of the organization